Power quality conditioning using two-level buck inverter based DSTATCOM - Suneetha, P.; Subbaramaiah, K.; Visali, Nagalamadaka (International Journal of Applied Power Engineering (IJAPE), 2024)
A two-level buck inverter is derived from the voltage source inverter, by replacing the additional power devices and suitable combination of inductor circuits respectively. Novel isolated buck inverter, featuring each-phase conversion and soft-switching within wide operation range, is developed. An optimized control strategy is employed to realize isolated buck conversion. By utilizing the buck inverter, the voltage stress on the power devices and passive components, the self-supported capacitor and filter inductance, is reduced to the half of the output voltage. Moreover, it is proven that the thyristor-controlled series capacitor (TCSC) equipped with a well-designed distributed static compensator (DSTATCOM) can effectively improve source current harmonics reduction, power factor correction in the source side, load compensation, regulation of load voltage and upholding constant voltage across the DC-link capacitor. In order to verify the effectiveness of the proposed DSTATCOM, its performance is compared with the two level DSTATCOM. The extensive simulations are carried out using MATLAB/Simulink to analyze the results. Experimental results using dSPACE-1104 prototype verify the appropriate DSTATCOM.